Felda Chuping non-revenue water management system - Ku-Mahamud, Ku Ruhana; Abu Bakar, Muhamad Shahbani; Wan Ishak, Wan Hussain (?, 2007)
Non-Revenue Water (NRW) is a part of water production but bring no revenue to the water authority. NRW control has been given high priority by the Malaysian Government. As NRW cannot be totally avoided, understanding and managing its components is very crucial. Felda Chuping water distribution system is taken as a case in this study. A conceptual model for treated water distribution system that consists of the configuration for water source, water storage, water network, and the supply area has been identified. The seven NRW components identified by International Water Association have been grouped into four different sections in the model.A comprehensive and flexible web based prototype has been developed for Felda Chuping water distribution system that incorporates function for data recording, NRW estimation and report generation.The prototype covers all aspect of water management which enables the water authority to use its output for decision making and planning.The prototype was developed based on two models, a framework and a work procedure for NRW analysis.